2015
DOI: 10.1007/s00787-015-0744-y
|View full text |Cite
|
Sign up to set email alerts
|

Social skills and psychopathic traits in maltreated adolescents

Abstract: Child maltreatment has frequently been associated with impaired social skills and antisocial features, but there are still controversies about the effect of each type of maltreatment on social behaviour. The aim of this study was to compare the social functioning and psychopathic traits of maltreated adolescents (MTA) with a control group (CG) and to investigate what types of maltreatments and social skills were associated with psychopathic traits in both groups. The types and intensity of maltreatment were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“… 67 Furthermore, these findings are in accordance with clinical studies indicating that childhood maltreatment is linked to impaired social skills 46 , 47 and is a strong predictor of later-life social behavior problems, including adolescent social withdrawal and adult antisocial behavior. 37 , 38 , 75 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 67 Furthermore, these findings are in accordance with clinical studies indicating that childhood maltreatment is linked to impaired social skills 46 , 47 and is a strong predictor of later-life social behavior problems, including adolescent social withdrawal and adult antisocial behavior. 37 , 38 , 75 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 , 19 , 20 , 21 , 22 Adverse early-life experiences involving the caregiver negatively affect the development of the amygdala 23 , 24 a critical brain area for emotion and social behavior 25 , 26 in humans 27 , 28 , 29 , 30 , 31 and other mammals. 24 , 32 , 33 , 34 , 35 Furthermore, maltreatment and abuse lead to social impairments, 36 , 37 , 38 , 39 which typically precede the onset of later-life psychopathology and serve as a predictive marker for later-life symptoms related to psychopathology. 40 , 41 Similar findings have been obtained using naturalistic rodent models of early-life stress that mimic maternal maltreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional abuse is also implicated in low self-esteem (Mullen, Martin, Anderson, Romans, & Herbison, 1996) and interpersonal difficulties (Dodge Reyome, 2010; Perry, DiLillo, & Peugh, 2007). However, multiple studies indicate that emotional neglect may be more strongly associated with social competence deficits than emotional abuse (Ometto et al, 2016; Paradis & Boucher, 2010).…”
Section: Effects Of Emotional Maltreatment On Psychopathology and Promentioning
confidence: 99%
“…Although it has been hypothesized that childhood maltreatment (CM) may lead to long-term alterations in interpersonal functioning (Briere & Jordan, 2009 ) including empathy, findings are presently mixed. For instance, whereas some studies suggest reduced empathy in maltreated children (Ometto et al, 2016 ), others found no deficits in empathic responding (McCloskey & Lichter, 2003 ). Similarly, whereas in some adult women with CM experience perspective-taking abilities and empathic concern are reduced, but personal distress is increased (Parlar et al, 2014 ), others documented higher empathic concern but lower personal distress (Hudson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%